Comparison of relative age of elite athletes participating in the 2008 Brazilian soccer championship series A and B - Costa,V.T. (2009)
The relative age of athletes has raised the attention of many researchers. The focus of these investigations understands the interference of this parameter in the identification of talents and the training of future elite athletes. Thus, the aim of this paper was to to evaluate and compare the existence of differences between semesters and birth date quartiles in professional soccer participating in the Brazilian Soccer Championship Series A (1st division) and B (2nd division) in 2008. Fourty clubs that participated in the Brazilian Soccer Championship Series A and B were evaluated, totalizing 1022 players (483 players in the 1st division and 539 players in the 2nd division). The players were grouped per birth date into year quartiles and semesters. The data showed that there was a preference of clubs from the two championship series for hiring athletes born in the 1st semester. Further, differences were absent only between quartiles 2 and 3 and a clubs` preference for 1st quartile athletes was also observed. We can conclude that the relative age stands out as a variable in the elite soccer athlete selection and training, as the comparisons show the clubs` preference for athletes born early in the year.